Cytomegalovirus Replication in Semen Is Associated with Higher Levels of Proviral HIV DNA and CD4(+) T Cell Activation during Antiretroviral Treatment - Gianella, Sara (American Society for Microbiology, 2014)
Asymptomatic cytomegalovirus (CMV) replication occurs frequently in the genital tract in untreated HIV-infected men and is associated with increased immune activation and HIV disease progression. To determine the connections between CMV-associated immune activation and the size of the viral reservoir, we evaluated the interactions between (i) asymptomatic seminal CMV replication, (ii) levels of T cell activation and proliferation in blood, and (iii) the size and transcriptional activity of the HIV DNA reservoir in blood from 53 HIV-infected men on long-term antiretroviral therapy (ART) with suppressed HIV RNA in blood plasma. We found that asymptomatic CMV shedding in semen was associated with significantly higher levels of proliferating and activated CD4(+) T cells in blood (P < 0.01). Subjects with detectable CMV in semen had approximately five times higher average levels of HIV DNA in blood CD4(+) T cells than subjects with no CMV. There was also a trend for CMV shedders to have increased cellular (multiply spliced) HIV RNA transcription (P = 0.068) compared to participants without CMV, but it is unclear if this transcription pattern is associated with residual HIV replication. In multivariate analysis, the presence of seminal plasma CMV (P = 0.04), detectable 2-long terminal repeat (2-LTR), and lower nadir CD4(+) (P < 0.01) were independent predictors of higher levels of proviral HIV DNA in blood. Interventions aimed at reducing seminal CMV and associated immune activation may be important for HIV curative strategies. Future studies of anti-CMV therapeutics will help to establish causality and determine the mechanisms underlying these described associations. IMPORTANCE Almost all individuals infected with HIV are also infected with cytomegalovirus (CMV), and the replication dynamics of the two viruses likely influence each other. This study investigated interactions between asymptomatic CMV replication within the male genital tract, levels of inflammation in blood, and the size of the HIV DNA reservoir in 53 HIV-infected men on long-term antiretroviral therapy (ART) with suppressed HIV RNA in blood plasma. In support of our primary hypothesis, shedding of CMV DNA in semen was associated with increased activation and proliferation of T cells in blood and also significantly higher levels of HIV DNA in blood cells. These results suggest that CMV reactivation might play a role in the maintenance of the HIV DNA reservoir during suppressive ART and that it could be a target of pharmacologic intervention in future studies.